A Comparative Study on the Derivation of Unit Hydrograph for Bharathapuzha River Basin. (2016) - Roy, Abhinanda; Thomas, Reeba
Abstract: Several techniques are available for the development of the unit hydrograph. But most of these traditional methods require manual fitting of the unit hydrograph through few points, which does not guarantee the area under the unit hydrograph to be unity. More over most of the stations are ungauged, due to which it becomes difficult to develop the unit hydrograph. So in order to overcome these problems, two methods have been considered in this study for the development of the unit hydrograph for Bharathapuzha river basin. They are the "two parameter Gamma distribution" and "three parameter Beta distribution", both of which are based on Probability Distribution Functions (pdfs). The unit hydrograph developed by the two parameter Gamma distribution match well with the one developed by CWC method, but the unit hydrograph developed by the three parameter Beta distribution does not match well with the one developed by the CWC method. From the unit hydrograph, runoff hydrograph is convoluted for the year 2008. For this the hourly rainfall are generated from daily rainfall values by disaggregation. But on plotting, the simulated discharge hydrograph is found to be greater than the observed discharge. This may be due to non incorporation of the inflow outflow processes of many hydraulic structures such as dams, irrigation schemes etc, existing in the basin in the model study. The data related to these structures could not be obtained due to certain restriction in acquiring the data from authorized agencies.